Clinicopathological study of malignancy in solitary thyroid nodule - Samson, Seuz C.; Kumar, Santhosh (Journal of clinical and investigative surgery, 2022)
Objectives. To study proportion of malignancy in patients with solitary thyroid nodule who had underwent hemi/total thyroidectomy. Methodology. Study design: Cross sectional study. Study setting: Patients in the Out-patient and In-patient Department of General Surgery, Government Medical College, Thiruvananthapuram. Sample size: 150 patients Study Procedure: Data was collected using a structured proforma. An informed consent written in the local language was read out to the study subjects and signature was obtained. All the questions in the proforma were read to the study subjects and responses recorded. Investigation reports and previous medical reports were used for filling relevant parts of the proforma. Analysis: Data collected was entered in excel sheets and analyzed using SPSS software. Results. 150 patients were operated for clinically detected STN. 16 (10.67%) were malignant. Papillary thyroid cancer was the most common type (93.75%). Mean age of patients with malignancy (n = 58) was 39.94 ± 14.83 years. Out of them 12 were females and 4 were male patients (F: M = 3: 1). 134 STNs were benign (23 males and 111 females). Malignant STN was reported in 14.81% males and 9.76% females. No significant correlation between tumour size and the risk of malignancy (P = 0.338). Altered thyroid function status is not a predictive factor for malignancy (P=0.801). FNAC (P=0.002) and USG (P=<0.001) were predictive of malignancy. Complications were more associated with total thyroidectomy (53.57%). Most frequent complication was transient hypocalcemia (15.4%). Hospital stay were more in patients who had underwent total thyroidectomy (P=<0.001). Conclusions. STN has high malignant potential compared to MNG. Preoperative evaluation with thorough history, physical examination, USG and FNAC could diagnose STN as benign or malignant. Strong predictors of malignancy include male gender, micro calcification and cervical lymphadenopathy. Complications are more associated with Total thyroidectomy. Hypocalcemia was the most common complication following thyroid surgery.